LOCAL WISDOM OF SEDULUR SIKEP (SAMIN) SOCIETYâ€™S MARRIAGE IN KUDUS: PERSPECTIVE OF LAW NUMBER 1 YEAR 1974 ON MARRIAGE - Hartanto, Dwiyana Achmad (Faculty of Law, Universitas Jenderal Soedirman, 2017)
The research entitled â€œLocal Wisdom of Sedulur Sikep (Samin) Societyâ€™s Marriage in Kudus: Perspective of Law Number 1 of 1974 on Marriageâ€ tried to reveal marriage practice of Sedulur Sikep (Samin) society in Kaliyoso, Karangrowo Village, Undaan Sub district, Kudus Regency. This research aims to (1) Find out the causal factors of why Sedulur Sikep (Samin) society in Kaliyoso, Karangrowo Village, Undaan Sub district, Kudus Regency unregister their marriage, (2) Discover the importance of marriage registration and find out the consequence of unregistered marriage. This research applied sociological juridical approach or empirical law research. The result of this research shows that Sedulur Sikep (Samin) society in Kaliyoso, Karangrowo Village, Undaan Subdistrict, Kudus Regency does not register their marriage since their custom or local wisdom does not recognize it which means that marriage registration is not an obligation. Marriage registration is crucial since it provides legal assurance toward any legal consequences appears due to marriage.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Keywords: local wisdom, marriage, sedulur sikep